Code-Mixing as an Expressive Strategy in Digital Spoken: A Case Study of Maudy Ayunda’s YouTube Channel - Citra Ratu Angelia Mustika Sari (Pustaka Digital Indonesia, 2026)
This study investigates the use of expressive code-mixing in Maudy Ayunda’s YouTube discourse, focusing on how bilingual language practices function as a medium for emotional expression and reflective storytelling in digital communication. Grounded in sociolinguistic theory, this research employs a qualitative descriptive method and adopts typology of code-mixing, which categorizes code-mixing into Insertion, Alternation, and Congruent Lexicalization. The data were collected from selected reflective videos on Maudy Ayunda’s YouTube channel and analyzed through transcription, identification, and contextual interpretation of code-mixed utterances. The findings reveal that Insertion is the most dominant type of code-mixing, accounting for 56.25% of the data, followed by Alternation at 43.75%, while Congruent Lexicalization was not found. These results indicate that Indonesian functions as the matrix language, with English serving as a complementary linguistic resource. Beyond structural patterns, the study demonstrates that code-mixing performs a significant expressive function. English elements are frequently employed to articulate emotions such as stress, relief, self-awareness, motivation, and emotional reassurance. Insertion is commonly used to intensify emotional states and describe complex psychological experiences, whereas Alternation allows the speaker to deliver reflections, evaluations, and conclusions more emphatically. The study concludes that code-mixing in Maudy Ayunda’s YouTube discourse extends beyond linguistic variation and operates as a strategic expressive tool that fosters emotional engagement and audience connection. This research contributes to sociolinguistic studies by highlighting the expressive and pragmatic roles of code-mixing in digital bilingual communication.